1979
DOI: 10.1063/1.90562
|View full text |Cite
|
Sign up to set email alerts
|

The etching of silicon with XeF2 vapor

Abstract: It is shown that silicon is isotropically etched by exposure to XeF2(gas) at T=300 K. Si etch rates as large as 7000 Å/min were observed for P (XeF2) <1.4×10−2 Torr and the etch rate varies linearly with P (XeF2). There was no observable etching of SiO2, Si3N4, or SiC, demonstrating an extremely large selectivity between silicon and its compounds. Therefore, thin masks constructed from silicon compounds can be used for pattern delineation. The implication of these experimental results for understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(108 citation statements)
references
References 9 publications
3
98
0
1
Order By: Relevance
“…12 Therefore a detailed modelling of the reaction is not feasible. Instead we will try to indicate the rate-limiting steps for the steady state etching process 27,28 and describe the reaction layer formation within the framework of the chain model. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Therefore a detailed modelling of the reaction is not feasible. Instead we will try to indicate the rate-limiting steps for the steady state etching process 27,28 and describe the reaction layer formation within the framework of the chain model. …”
Section: Discussionmentioning
confidence: 99%
“…At low temperatures there is no desorption of SiF 2 , the fluorine content of the reaction layer is constant and the etch rate, i.e., SiF 4 production, is limited by the XeF 2 -precursor concentration. 27,28 At high temperatures the change in the desorption rate of the XeF 2 -precursor can be neglected and the etch rate is limited by the desorption of SiF 2 . This results in the following equations:…”
Section: A Reaction Mechanismmentioning
confidence: 99%
“…Because of its high etch rate and high selectivity against many metals, dielectrics, and polymers used in traditional integrated circuit fabrications, XeF 2 has been a widely used to etch Silicon isotropically etchant in microelectromechanical systems (MEMS) 1 processing since 1995 2 . XeF 2 is also used as a fluorination reagent in organic chemistry, due to its mild reactivity and high selectivity 3,4 While XeF 2 is a good etchant of silicon 5 , Al and Al 2 O 3 are among the materials which are not etched by XeF 2 and therefore are commonly used as structural materials.…”
mentioning
confidence: 99%
“…From the linear dependence of the etch rate on the XeF 2 flow over a wide range, 22 it is concluded that the physisorbed XeF 2 concentration is very low at room temperature.…”
Section: Mechanisms Of Sif 4 Enhancement: Discussionmentioning
confidence: 99%